(untitled) (Tribhuvan University Journal of Microbiology, 2018)
Objective: To determine the microbial quality of milk available in market of Janakpurdham, Nepal. Methods: Total 20 samples of milk were collected aseptically from the market and processed for MBRT test as per standard protocol given in a monograph. Reduction time test for each sample of the milk was recorded in a specified format and analysed statistically. Result: Out of 20 samples, 2 (10%) samples were found excellent quality, 3 (15%) were of good quality, 6 (30%) were of fair quality and 9 (45%) were of poor quality. Among these 20 samples, 6 samples were of processed milk, 5 samples were of unprocessed/raw milk and 9 samples were of DDC milk. Unprocessed milk was found to be highly contaminated in comparison to the processed milk. Conclusion: Unprocessed milk was found to be highly contaminated and not fi t for the human consumption.